Analysis of Factors Influencing the Existence of Baitul Maal wa Tamwil (BMT) - Trihudiyatmanto, M. (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to see the effect of regulation, supervision, institutional capacity on the existence of BMTs in Wonosobo. The data used in this study by distributing questionnaires directly to BMT employees in Wonosobo.Method - The population in this study were all 291 BMT employees. After passing the probability sampling, the sample in this study were 74 employees who worked at BMT Wonosobo. The analytical method used in this study is multiple linear regression, then using descriptive statistical tests, validity tests, reliability tests, goodness of fit tests, classic assumption tests which include: normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing including coefficient test determination and significant test of the regression coefficient with a significance f of 5%.Result - The results of this study indicate that regulation, supervision, and capacity have a positive effect on the existence of BMT.Implication - The results of this study are expected to provide benefits to companies, to contribute to the factors that influence the existence of BMT so that they can make the right decisions and policies to make them more optimal.Originality- Research on assessment Existence of BMT with view of regulation and supervision.